2022
DOI: 10.3389/fnmol.2022.882443
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-3-Glucuronide, Physiology and Behavior

Abstract: Morphine remains the gold standard painkiller available to date to relieve severe pain. Morphine metabolism leads to the production of two predominant metabolites, morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G). This metabolism involves uridine 5′-diphospho-glucuronosyltransferases (UGTs), which catalyze the addition of a glucuronide moiety onto the C3 or C6 position of morphine. Interestingly, M3G and M6G have been shown to be biologically active. On the one hand, M6G produces potent analgesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 158 publications
(219 reference statements)
0
12
0
Order By: Relevance
“…In mammals, hydromorphone is metabolized primarily by conjugation with glucuronic acid to form the metabolite H3G in a similar manner to morphine that forms morphine-3-glucuronide (M3G), the main metabolite of morphine. 20 In the study reported here, H3G was detectable in all birds at 30 minutes following drug administration by both the IV and IM routes and had measurable plasma concentrations up to 12 hours postadministration, which was the last time point measured. The quantifiable concentrations of this metabolite suggest that hydromorphone in GHOWs may have a similar metabolic profile as mammals.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In mammals, hydromorphone is metabolized primarily by conjugation with glucuronic acid to form the metabolite H3G in a similar manner to morphine that forms morphine-3-glucuronide (M3G), the main metabolite of morphine. 20 In the study reported here, H3G was detectable in all birds at 30 minutes following drug administration by both the IV and IM routes and had measurable plasma concentrations up to 12 hours postadministration, which was the last time point measured. The quantifiable concentrations of this metabolite suggest that hydromorphone in GHOWs may have a similar metabolic profile as mammals.…”
Section: Discussionmentioning
confidence: 52%
“…It is unknown if H3G has analgesic effects; however, the structural analog M3G has been associated with neuroexcitant signs in rats without analgesic effects. In contrast, the morphine metabolite morphine-6-glucuronide has been associated with analgesic effects, 20,42 but an analgesic analog metabolite has not been identified for hydromorphone. A study 41 investigating the neuroexcitant effects of H3G in rats revealed that it can induce dose-dependent-excitatory behaviors such as myoclonus, changes in body postures, and tonic-clonic seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that morphine antinociception and tolerance, as well as its metabolism in the brain, are influenced by sex [31]. In the brain, morphine is metabolized into its predominant metabolite M3G which is believed to oppose morphine effects ( i.e ., produces hyperalgesia) [32]. Although M3G mechanism of action remains unclear, several studies have suggested an alteration of neurotransmission as a consequence of M3G effects (for review, see Gabel 2022).…”
Section: Introductionmentioning
confidence: 99%
“…M3G displays a relatively low affinity for opioid receptors and has no analgesic activity. In fact, an opposite effect, hyperalgesia, has been reported (Frölich et al, 2011; Gabel et al, 2022). M6G, however, is capable of eliciting profound analgesic activity, and has even been propose to as the main drive of the analgesic effects of morphine treatment (Klimas and Mikus, 2014; Murthy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%